Optimizing Digital Marketing and Service Quality to Strengthen Customer Loyalty in Rural Banks’ Digital Transformation Era - Nursamawi Nursamawi; Lucky Hikmat Maulana; Bramastyo Bontas Prastowo (International Journal of Management Science and Information Technology, 2026)
This study examines the effects of digital marketing and service quality on customer loyalty, with customer satisfaction serving as a mediating variable, at Perumda Bank Perekonomian Rakyat (BPR) Bank Kota Bogor, Indonesia. The study is motivated by the increasing digital transformation in the banking industry and the growing competition from fintech companies and digital banks, which require rural banks to strengthen customer relationships and maintain competitiveness. A quantitative explanatory approach was employed using survey data collected from 100 active customers selected through purposive sampling to ensure respondents had experience using the bank’s digital services. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), which was considered suitable for examining complex relationships among variables with a relatively small sample size. The findings reveal that service quality has a positive and significant effect on customer satisfaction and customer loyalty, while customer satisfaction significantly influences customer loyalty and mediates the relationship between service quality and loyalty. In contrast, digital marketing does not significantly affect customer satisfaction, although it directly influences customer loyalty. Furthermore, customer satisfaction does not mediate the relationship between digital marketing and customer loyalty. These findings indicate that customer loyalty in rural banking is driven more by service quality and customer satisfaction than by digital marketing activities alone. This study contributes to the limited literature on customer loyalty in rural banking and provides practical insights for bank management in strengthening service quality and optimizing digital marketing strategies to enhance long-term customer relationships.